PENGGUNAAN MEDIAN PADA PERLINTASAN SEBIDANG UNTUK MENGURANGI PELANGGARAN PINDAH LAJUR (STUDI KASUS DI PERLINTASAN JALAN A.R. HAKIM KOTA TEGAL) - Kurniawan, Hanung; Prasetianto, Eko; Nurhakim, Rifki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The number of accidents in railway crossings lately, is of particular concern for us to examine the phenomenon that the caused the accident, then we do research at railway crossings in the city of Tegal. Survey Methods used in this study is the direct observation. while Average Daily Traffic data (ADT) is used Secondary data, from the 2013 survey PKTJ Midshipman. In this study using the method of analysis "Before and After" The results of the analysis of three experimental treatments (30, 60, and 90 meters) to decrease violations on level crossings, the result  of the experiment that the ideal length of median which is used at rail way crossings on both Jalan A.R Hakim and Jalan Sultan Agung is 60 meters because based on the result analysis, it is more effective to decrease the number lanes violation than the median which length is 30 meters and 90 meters.